Oxidative stress and starvation in Dinoroseobacter shibae: the role of extrachromosomal elements - Soora, Maya; Tomasch, Jürgen; Wang, Hui; Michael, Victoria; Petersen, Jörn; Engelen, Bert; Wagner-Döbler, Irene; Cypionka, Heribert (Frontiers in Microbiology, 2015)
Aerobic anoxygenic phototrophic bacteria (AAP) are abundant in the photic zone of the marine environment. Dinoroseobacter shibae, a representative of the Roseobacter group, converts light into additional energy that enhances its survival especially under starvation. However, light exposure results in the production of cytotoxic reactive oxygen species in AAPs. Here we investigated the response of D. shibae to starvation and oxidative stress, focusing on the role of extrachromosomal elements (ECRs). D. shibae possessing five ECRs (three plasmids and two chromids) was starved for four weeks either in the dark or under light/dark cycles and the survival was monitored. Transcriptomics showed that on the chromosome genes with a role in oxidative stress response and photosynthesis were differentially expressed during the light period. Most extrachromosomal genes in contrast showed a general loss of transcriptional activity, especially in dark-starved cells. The observed decrease of gene expression was not due to plasmid loss, as all five ECRs were maintained in the cells. Interestingly, the genes on the 72-kb chromid were the least downregulated, and one region with genes of the oxygen stress response and a light-dependent protochlorophyllide reductase of cyanobacterial origin was strongly activated under the light/dark cycle. A Δ72-kb curing mutant lost the ability to survive under starvation in a light/dark cycle demonstrating the essential role of this chromid for adaptation to starvation and oxidative stress. Our data moreover suggest that the other four ECRs of D. shibae have no vital function under the investigated conditions and therefore were transcriptionally silenced.